From Pesantren to Parliament: The Political Landscape of Nahdlatul Ulama during Indonesia’s New Order (1973–1998) - Ahmad Shihafun Ni'am; Miftahuddin Miftahuddin (Yupa: Historical Studies Journal, 2025)
This article aims to investigate the intertwining of NU and politics during the New Order era. The research was conducted using a qualitative method with a Historical Science approach. The results indicate that during the New Order period, Nahdlatul Ulama (NU) played an important role in Indonesian politics. After breaking away from the Masyumi Party in 1952, NU established its own political party and won 45 seats in the 1955 General Election. Despite the collapse of the Old Order, NU remained active in politics during the New Order era. Idham Chalid, one of NU's leaders, served as Minister of People's Welfare (1967-1970) and Minister of Social Affairs (1970-1971) in the first New Order cabinet. However, the New Order government's party simplification policy in 1971 resulted in the fusion of several parties, including NU, into the United Development Party (PPP). Despite this, the NU maintained its influence through the PPP and continued to play a role in national politics. The NU's involvement in politics during the New Order era demonstrated the organization's adaptation to dynamic political change.